2018
DOI: 10.1186/s12910-018-0326-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges arising when seeking broad consent for health research data sharing: a qualitative study of perspectives in Thailand

Abstract: BackgroundResearch funders, regulatory agencies, and journals are increasingly expecting that individual-level data from health research will be shared. Broad consent to such sharing is considered appropriate, feasible and acceptable in low- and middle-income settings, but to date limited empirical research has been conducted to inform the design of such processes. We examined stakeholder perspectives about how best to seek broad consent to sharing data from the Mahidol Oxford Tropical Medicine Research Unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Broad consent could be valid if there was some clarity at the time of consent, the kinds of people, or institutions to be shared with, and how, in broad terms, the data would likely be used. 28 , 29 In this study, only about half of the researchers rated the use of broad consent in acquiring data for sharing as very important. It is postulated that many researchers might have usually applied broad consent in their studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Broad consent could be valid if there was some clarity at the time of consent, the kinds of people, or institutions to be shared with, and how, in broad terms, the data would likely be used. 28 , 29 In this study, only about half of the researchers rated the use of broad consent in acquiring data for sharing as very important. It is postulated that many researchers might have usually applied broad consent in their studies.…”
Section: Discussionmentioning
confidence: 81%
“… 40 A qualitative study among stakeholders of a research unit based in Thailand demonstrated that clinical-trial participants mainly focused on information about the potential benefits and harms of data-sharing and how much information should be provided about data-sharing. 28 It is important to have effective, valid, consent process. Broad consent could be valid if there was some clarity at the time of consent, the kinds of people, or institutions to be shared with, and how, in broad terms, the data would likely be used.…”
Section: Discussionmentioning
confidence: 99%
“…Our normative proposal is supported by experience of establishing and coordinating the Mahidol Oxford Tropical Medicine Research Unit (MORU) DAC, which has reviewed over 40 applications since its establishment in January 2016 [51][52][53]. The MORU DAC has reviewed many types of data requests including data in real time from an ongoing clinical study, from historical trials done without participant consent for data sharing, and from pharmaceutical companies for data from trials conducted in low-resource settings for registering products in developed countries [52,54].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, from our experience and that of others conducting studies in LMICs, participants rarely fully comprehend the information in primary studies [2224]. Our recent empirical study showed that providing information on data sharing and obtaining broad consent for data sharing in addition to the consent for the primary study adds another layer of complexity to the consent process [25].…”
Section: Elements Of a Data Management And Sharing Policymentioning
confidence: 99%